2023
DOI: 10.3390/microorganisms11030563
|View full text |Cite
|
Sign up to set email alerts
|

Avian Malaria Parasites Modulate Gut Microbiome Assembly in Canaries

Abstract: Rodent and human malaria parasites cause dysbiosis in the host gut microbiome, but whether Plasmodium species affecting birds cause dysbiosis in their hosts is currently unknown. Here we used a model of avian malaria infection to test whether parasite infection modulates the bird microbiome. To this aim, bird fecal microbiomes were characterized at different time points after infection of canaries with the avian malaria parasite Plasmodium homocircumflexum. Avian malaria caused no significant changes in the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 78 publications
3
11
1
Order By: Relevance
“…Studies comparing some of the methods (i.e., PICRUSt, PICRUSt2, and Tax4Fun) revealed that no method was superior to another [ 76 ], and PICRUSt2 has been applied on samples from various animals, including arthropods (e.g., Ixodes spp. [ 77 ], nematodes (e.g., Caenorhabditis elegans , [ 78 ]), birds (e.g., Serinus canaria domestica [ 79 ]), and mammals (e.g., humans [ 39 ], goats [ 80 ], and bats [ 21 ], among others. In our study, analysis of the functional prediction for multiple bat species, which are taxonomically different and have distinct feeding strategies, showed that frugivorous bats are very different from insectivorous, carnivores, or blood-feeders.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing some of the methods (i.e., PICRUSt, PICRUSt2, and Tax4Fun) revealed that no method was superior to another [ 76 ], and PICRUSt2 has been applied on samples from various animals, including arthropods (e.g., Ixodes spp. [ 77 ], nematodes (e.g., Caenorhabditis elegans , [ 78 ]), birds (e.g., Serinus canaria domestica [ 79 ]), and mammals (e.g., humans [ 39 ], goats [ 80 ], and bats [ 21 ], among others. In our study, analysis of the functional prediction for multiple bat species, which are taxonomically different and have distinct feeding strategies, showed that frugivorous bats are very different from insectivorous, carnivores, or blood-feeders.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria, caused by various strains of malaria parasites such as Plasmodium falciparum, Plasmodium vivax, Plasmodium ovale, Plasmodium malariae, and Plasmodium knowlesi, is a major threat to human health worldwide. It is estimated that around 3.3 billion people are at risk of developing this disease [1]. Recent research on the human microbiome has revealed a link between resident microbial communities and the risk of blood parasites, offering potential for microbialbased disease treatments such as probiotics [2].…”
Section: Commentarymentioning
confidence: 99%
“…The immune response plays a crucial role in the pathophysiology of malaria. While chloroquine was once the drug of choice for treating P. falciparum malaria, the emergence of resistance among this species has made it less effective [1]. Probiotics are microorganisms that provide health benefits to consumers.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…This concept considers their interactions over time, as well as the inherent feedback mechanisms between hosts, their microbiome, and the surrounding environment [24]. Disruptions of these early-life microbiome assembly processes can adversely affect the host [55,99] by influencing immune system development [41,54], and diminishing resistance to parasitic infections [7,78]. Understanding the factors influencing avian gut microbial composition in early life is therefore of great importance due to the potential long-term impacts of the gut microbiota on host development and body condition [55,77].…”
Section: Introductionmentioning
confidence: 99%